Acute to post-acute COVID-19 thromboinflammation persistence: Mechanisms and potential consequences - Remy Martins-Gonçalves; Eugenio D. Hottz; Patricia T. Bozza (Current Research in Immunology, 2023)
Concerns for the long-term effects of COVID-19 infection have grown due to frequently reported persisting symptoms that can affect multiple systems for longer than 4 weeks after initial infection, a condition known as long-COVID-19 or post-acute COVID-19 syndrome (PACS). Even nonhospitalized survivors have an elevated risk for the development of thromboinflammatory-associated events, such as ischemic stroke and heart failure, pulmonary embolism and deep vein thrombosis. Recent findings point to the persistence of many mechanisms of hypercoagulability identified to be associated with disease severity and mortality in the acute phase of the disease, such as sustained inflammation and endotheliopathy, accompanied by abnormal fibrin generation and impaired fibrinolysis. Platelets seem to be central to the sustained hypercoagulable state, displaying hyperreactivity to stimuli and increased adhesive capacity. Platelets also contribute to elevated levels of thromboinflammatory mediators and pro-coagulant extracellular vesicles in individuals with ongoing PACS. Despite new advances in the understanding of mechanisms sustaining thromboinflammation in PACS, little is known about what triggers this persistence. In this graphical review, we provide a schematic representation of the known mechanisms and consequences of persisting thromboinflammation in COVID-19 survivors and summarize the hypothesized triggers maintaining this prothrombotic state.